A blurred border between ordinary concrete and SFRC. (1st June 2016) - Domski, Jacek
Highlights: The minimum volume of fibres that was used had a positive effect on improving residual strength. Minimum volume of fibre which would transform ordinary concrete into SFRC. Mechanical properties of SFRC in time. Application of class SFRC according to Model Code 2010. Reduction of the aggregate cost and preservation of the environment by valorizing waste sand. Abstract: Steel fibre reinforced concrete is a well-established construction material. So far its specific properties have been defined and assessed using multiple, literature defined factors and limits. In 2010 there was published fib Model Code which defines strength classes SFRC. The strength classes are based on values of residual strength tested according to EN 14651. Thus it is now possible to tackle SFRC properties in a very precise way. In the paper the research programme aims to define the blurred border between ordinary concrete and SFRC (made on the basis of aggregate of a largest size of 4 mm). The main goal was to get a minimum critical volume of fibre which would transform ordinary concrete into SFRC with an official strength class.